Distance spectra of convolutional codes over partial-response channels. - Despotovic, M.
This paper is concerned with the well-known coding technique that uses cosets of convolutional codes along with precoding to increase the free squared Euclidean distance at the output of a partial-response channel. The focus is on totally trellis-matched codes, for which the decoding trellis has the fewest number of states. Codes totally trellis-matched to the extended partial-response class 4 (EPR4) and the doubly extended partial-response class 4 (E2PR4) channels for a variety of code rates and overall constraint lengths are sought for with respect to the squared Euclidean distance spectrum criterion. Furthermore, some previously published codes are shown to contain flawed codewords and are replaced with new ones
Keywords: E2PR4 channel; E2PR4 channel; EPR4 channel; Channel coding; Code constraint lengths; Code rates; Codewords; Computational complexity; Convolutional codes; Decoding trellis; Doubly extended partial-response class 4.; Extended partial-response class 4 channel; Free squared Euclidean distance; Partial-response channels; Precoding; Squared Euclidean distance spectrum; Trellis-matched codes